Gendering indigenous subjects: an institutional ethnography of corporate social responsibility in Ecuador. Issue 8 (2nd August 2020) - Billo, Emily
Abstract: Corporate social responsibility (CSR) programs are institutions of governance and development designed to respond to socio-ecological impacts of resource extraction. I argue that CSR programs are an overlooked tool of the neoliberal project of gendered indigenous subject formation in Ecuador. The article contributes to feminist political ecology through its use of institutional ethnography, a feminist methodology. It advances feminist commitments to everyday, embodied analyses of resource struggles, illustrating how gender and indigeneity are intersectional subjectivities provoked by the socio-spatial relationships of CSR programs. Postcolonial intersectional analysis of CSR programs demonstrates how power expands through gender and indigeneity contributing to indigenous women's ongoing marginalization in Ecuador.